Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s00415-011-6261-0
|View full text |Cite
|
Sign up to set email alerts
|

Case–control study of blink rate in Parkinson’s disease under different conditions

Abstract: Standard neurology texts list a reduced blink rate as one of the clinical features of Parkinson's disease. However, there are few clinical studies which have quantified this clinical sign. Here we present the results of a quantified study in a cohort of cases and controls using a standard protocol. Cases meeting standard criteria for a diagnosis of Parkinson's disease were studied together with age- and sex-matched controls. Baseline data included age, sex, duration of disease, Hoehn and Yahr stage, mini-menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 24 publications
(39 reference statements)
2
23
1
Order By: Relevance
“…Fitzpatrick assessed the BR in patients with PD during different tasks such as watching a video, being interviewed, and reading from a book and found that BR was significantly reduced in the patients with PD compared to the healthy controls for each of the test conditions but there was no effect of disease duration, severity or treatment on BR [20]. As previously described [8,[18][19][20], in our study, we found that the patients with PD had significantly reduced BR than healthy controls and there was a significantly negative association between the BR and disease severity.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Fitzpatrick assessed the BR in patients with PD during different tasks such as watching a video, being interviewed, and reading from a book and found that BR was significantly reduced in the patients with PD compared to the healthy controls for each of the test conditions but there was no effect of disease duration, severity or treatment on BR [20]. As previously described [8,[18][19][20], in our study, we found that the patients with PD had significantly reduced BR than healthy controls and there was a significantly negative association between the BR and disease severity.…”
Section: Discussionmentioning
confidence: 96%
“…Studies reported that patients with PD had reduced blink rates compared to normal subjects, with longer pauses in voluntary blinking, small amplitude and peak velocity in spontaneous blinking [8,18,19]. A decreased BR is thought to be one of the clinical features of PD [20]. It has been suggested that this may be related to hypokinesia from decreased dopamine levels in the central nervous system [21].…”
Section: Discussionmentioning
confidence: 97%
“…Additional support for the association between EBR and dopamine come from observations of aberrant EBR in individuals with neurologic or psychiatric disorders linked to dopaminergic dysfunction (e.g., Parkinson’s disease and schizophrenia), or a history of using drugs known to affect the dopamine system (e.g., cocaine; Chen et al, 1996 ; Colzato et al, 2008 ; Kowal et al, 2011 ; Fitzpatrick et al, 2012 ). This evidence is complicated by the fact that aberrant EBR is also present in nondopamine specific conditions such as intellectual disability and traumatic brain injury ( Goldberg et al, 1987 ; Daugherty et al, 1993 ; Konrad et al, 2003 ), suggesting that EBR is influenced by and reflective of multiple brain processes (see Jongkees and Colzato, 2016 for a more thorough review of evidence relating EBR to dopamine).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced and increased dopamine activity is directly associated with low and high EBR, respectively (Groman, James, Seu, Tran, Clark, Harpster, et al, 2014;Karson, 1983;1992). The decrease in blink rate in Parkinson' Disease, a condition characterized by progressive severe loss of dopaminergic neurons in the striatum (Dauer and Przedborski, 2003), is considered a classical example of EBR and dopamine association (Fitzpatrick, Hohl, Silburn, O'Gorman, & Broadley, 2012). While there is variability in the way EBR is measured, one of the most frequently used methods is direct observation and counting by a researcher (Jongkees & Colzato, 2016).…”
Section: Introductionmentioning
confidence: 99%